2019
DOI: 10.1002/qj.3671
|View full text |Cite
|
Sign up to set email alerts
|

Comparing ground‐based observations and a large‐eddy simulation of shallow cumuli by isolating the main controlling factors of the mass flux distribution

Abstract: The distribution of mass flux at the cloud base has long been thought to be independent of large‐scale forcing. However, recent idealized modelling studies have revealed its dependence on some large‐scale conditions. Such dependence makes it possible to isolate the observed large‐scale conditions, which are similar to those in large‐eddy simulations (LES), in order to compare the observed and modelled mass flux distributions. In this study, we derive for the first time the distribution of the cloud‐base mass f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…the TSI cloud fraction and by 60 % compared to the AR-SCL value-added product. This general underestimation is also present in the original LASSO simulations as shown by Gustafson et al (2020) and matches the experience of previous continental shallow cumulus LES studies over the ARM-SGP site (Zhang et al, 2017) and over Cabauw in the Netherlands (Schalkwijk et al, 2015). Recently, Fast et al (2019) showed that using a more realistic surface moisture distribution leads to larger and longer-lived clouds, indicating that our cloud underestimation could be due to the homogeneous surface conditions of the LASSO setup.…”
Section: Simulation Evaluationsupporting
confidence: 88%
See 2 more Smart Citations
“…the TSI cloud fraction and by 60 % compared to the AR-SCL value-added product. This general underestimation is also present in the original LASSO simulations as shown by Gustafson et al (2020) and matches the experience of previous continental shallow cumulus LES studies over the ARM-SGP site (Zhang et al, 2017) and over Cabauw in the Netherlands (Schalkwijk et al, 2015). Recently, Fast et al (2019) showed that using a more realistic surface moisture distribution leads to larger and longer-lived clouds, indicating that our cloud underestimation could be due to the homogeneous surface conditions of the LASSO setup.…”
Section: Simulation Evaluationsupporting
confidence: 88%
“…-Compared to observations, MicroHH in combination with the LASSO forcing leads to a lower cloud fraction (similar to Schalkwijk et al, 2015;Zhang et al, 2017;Gustafson et al, 2020) and slightly shorter cloud chords.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…1 m s −1 also marks the upper tail of cloud-base averaged updraft vertical velocities at the BCO (see Fig. 4b of Sakradzija and Klingebiel, 2020). This suggests that the gust-front vertical velocity maxima are very relevant for triggering new convection in the trade cumulus regime.…”
Section: Composite Temporal Structurementioning
confidence: 73%
“…The average cold-pool passage is characterized by a 0.9 K temperature drop, a 0.2 g kg −1 humidity increase just before and another 0.2 g kg −1 humidity increase right after the front onset, followed by a −0.4 g kg −1 humidity decrease at the end of the front, wind speed and pressure increases of 1.15 m s −1 and 9 Pa, and rain intensities of 0.9 mm h −1 . The vertical velocity at the sub-cloud layer top shows pronounced maxima of 1 m s −1 near the cold-pool onset, which lies in the upper tail of cloud-base averaged updraft velocities at the BCO (Sakradzija and Klingebiel, 2020) and thus is very relevant for triggering new convection. The second half of the front is marked by sub-cloud layer averaged downdrafts of −0.55 m s −1 .…”
Section: Discussionmentioning
confidence: 99%